Еволюція наукових засад міжнародного бізнесу - Данько, Тарас Володимирович (ФОП Лібуркіна Л. М., 2019)
В Україні, починаючи з 1990-х років, спостерігається поступове зростання наукового інтересу до міжнародного бізнесу, але кількість відповідних праць досі залишається порівняно незначною. Водночас за кордоном наука про міжнародний бізнес з моменту появи у 1950-х роках пройшла значний шлях розвитку. В цьому контексті перед вітчизняними науковцями постає особливе завдання проаналізувати світові здобутки в цій галузі та на цій основі привести свою дослідницьку проблематику у відповідність до світових вимог сучасного етапу еволюції наукових засад міжнародного бізнесу. Незважаючи на значну кількість зарубіжних праць, присвячених дослідженню еволюції наукових засад міжнародного бізнесу, на сьогодні не існує єдиного усталеного підходу до класифікації етапів цього процесу. Це зумовило мету цього дослідження, а саме уточнити й узагальнити ключові характеристики основних етапів еволюції наукових засад міжнародного бізнесу з моменту появи цієї наукової дисципліни по теперішній час. Проведений аналіз з позицій інструменталістського підходу дозволив зробити висновок про те, що еволюція наукових засад міжнародного бізнесу є невідривною від міжнародного життєвого циклу цієї галузі та на цей момент має такі чотири етапи: інституалізація; бурхливе зростання; зрілість; ренесанс. В статті виділено й обґрунтовано часові рамки кожного етапу, та всебічно охарактеризовано кожний з них.

Since the 1990s, a gradual increase in scientific interest in international business has been observed in Ukraine, but the number of relevant research works is still relatively low. At the same time, in the rest of the world, the science of international business has made a remarkable path of development since the moment of its emergence in the 1950s. In this context, Ukrainian scientists have the special task of analyzing international achievements in this discipline and, based on this, bringing the focus of their research in compliance with the worldwide requirements at the modern stage of the scientific foundations evolution of international business. Despite a significant amount of international research papers that deal with studying the scientific foundations evolution of international business, there is no single well-established approach to classifying the stages of this process today. This predetermined the aim of the study, namely, to clarify and summarize the key characteristics of the basic stages in the scientific foundations evolution of international business from the moment of emergence of this scientific discipline to the present. The analysis carried out from the perspective of an instrumentalist approach has led to the conclusion that the scientific foundations evolution of international business is inseparable from the international life cycle of this discipline and currently comprises the following four stages: institutionalization; rapid growth; maturity; renaissance. In the article, the time frames of each stage are identified and justified, each of them being comprehensively characterized.
Scientific foundations evolution of international business
Keywords: глобалізація; інтернаціоналізація; менеджмент мультинаціональної компанії; міжнародне підприємництво; зовнішньоекономічна діяльність; evolution of science; globalization; internationalization; multinational company management; international entrepreneurship